Prevalence and antibiotic resistance patterns of Pseudomonas aeruginosa and Acinetobacter baumannii strains isolated from chicken droppings on poultry farms in Gondar city, Northwest Ethiopia - Mitkie Tigabie; Muluneh Assefa; Yalewayker Gashaw; Azanaw Amare; Aklilu Ambachew; Sirak Biset; Feleke Moges (Science in One Health)
Background: Pseudomonas aeruginosa and Acinetobacter baumannii are common nosocomial pathogens in hospital settings. Recently, they have also been found in non-hospital environments, such as poultry farms. While most studies in Ethiopia have focused on these bacteria's antibiotic resistance patterns in hospitals, information regarding their prevalence and resistance in veterinary settings, particularly poultry farms, is limited. This study aimed to assess the prevalence and antibiotic resistance patterns of P. aeruginosa and A. baumannii isolated from chicken droppings on poultry farms. Methods: A cross-sectional study was conducted from March 2022 to June 2022. A total of 87 poultry farms were included in this study, and pooled chicken dropping samples were collected. The samples were subsequently transferred to buffered peptone water and cultured on MacConkey agar. Species of the isolates were identified via routine biochemical tests, including oxidase, catalase, urease, Simon's citrate, sulfide indole motility medium, triple sugar iron agar and growth at temperatures of 37 °C and 42 °C. The Kirby–Bauer disk diffusion technique was used for antibiotic susceptibility testing. The data were entered into EpiData version 4.6 and then exported to SPSS version 26 for analysis. Fisher's exact test was used to observe an appropriate association between independent variables and the occurrence of isolates. The results are presented in the text, figures and tables. Results: Among the 87 poultry farms, 41 (47.1 %) were positive for Pseudomonas and Acinetobacter. Among these strains, 24 (27.6 %) P. aeruginosa strains and 13 (14.9 %) A. baumannii strains were recovered. P. aeruginosa showed complete resistance to tetracycline (24, 100.0 %) and trimethoprim-sulfamethoxazole (24, 100.0 %). Additionally, there was a high rate of resistance to ciprofloxacin (13, 54.2 %) and amikacin (12, 50.0 %). Similarly, 13 (100.0 %) A. baumannii isolates were resistant to tetracycline, and 12 (92.3 %) were resistant to trimethoprim-sulfamethoxazole. However, both isolates presented lower resistance rates to piperacillin-tazobactam (4, 9.8 %) and cefepime (7, 17.1 %). Both A. baumannii and P. aeruginosa exhibited multidrug resistance in 10/13 (76.9 %) and 16/24 (66.7 %) of the strains, respectively. The overall prevalence of multidrug resistance in this study was 28/41 (68.3 %). Conclusion: This study demonstrated that poultry farms may be potential reservoirs for P. aeruginosa and A. baumannii, including antibiotic-resistant strains. This is a significant concern to public health because poultry farmers may be contaminated, increasing their dissemination to the community. Therefore, poultry farmers should improve sanitation and reduce the misuse and overuse of antibiotics at poultry farms.